Background Chemical Study of Relocated Hazaribagh Tannery Complex Environment, Savar (Journal of Bangladesh Academy of Sciences, 2012)
A background study of the chemical constituents of some environmental samples - tannery   complex sand, river water, river sediment and river fishes collected from the Relocated Hazaribagh   Tannery Complex (RHTC) area, was carried out. In sand samples the mean values for pH, EC and   soluble salts were found to be 8.49, 0.02 mS/cm and 11.72 mg/kg and the mean concentrations of   elements K, Ca, Ti, Mn, Fe, Co, Zn, As, Pb, Rb and Sr were 94.8, 68.5, 16.6, 2.68, 129, 1.19,   0.23, 0.70, 0.32, 0.62 and 1.03 mg/kg, respectively. In river water samples the average   concentrations of K, Ca, Mn, Fe, Zn, As, Rb, Sr, SO 4 -2, PO4 -3, Cl-1 and NO3 -1 were 13.09, 178,   0.41, 1.82, 0.073, 0.031, 0.010, 0.48, 0.057, 0.019, 15.6, 5.68 mg/l and the average values for pH,   EC, DO, BOD, SS and DS were 8.02 and 0.35 mS/cm, 6.29, 4.21, 0.06, 0.36 mg/l, respectively.   The elements K, Ca, Ti, Cr, Mn, Fe, Ni, Cu, Zn, As, Rb, Sr and Pb were measured in river sediment   samples at the limit of 205, 155, 67, 6.02, 17.2, 798, 1.10, 1.24, 1.99, 0.31, 2.34, 2.63 and 0.35   mg/kg, respectively. In some locally available fishes like tengra, puti, baim, taki, shrimp, chanda   and baila, only the elements K, Ca, Fe, Zn, Rb and Sr could be measured in all species of fishes in   the range of 0.39 - 1.01, 0.68 - 2.29, 60.6 - 125, 46.3 - 174, 2.84 - 61.8 and 12.3 - 38.0% in mg/kg,   respectively. In the light of the overall study, the chemical constituent levels of the environmental   samples of the RHTC area at present are low and the environment is not yet contaminated. DOI: http://dx.doi.org/10.3329/jbas.v36i1.10919Journal of Bangladesh Academy of Sciences, Vol. 36, No. 1, 45-51, 2012